STUDY OF SOME PHYSICO–CHEMICAL PARAMETERS OF DHAMAPUR LAKE MALWAN, SINDHUDURGA DISTRICT, MAHARASHTRA (Indo-American Journal of Life Sciences and Biotechnology, 2025)
Present investigation deals with the study of physic-chemical parameters of Dhamapur lake in Malvan Sindhudurg Distrct, Maharashtra, The lake water is used for drinking, agriculture and other domestic purpose. The samples were collected from the station during the period of January 2023 to December 2023. The parameters Selected were Temperature, PH conductivity, BOD, Hardness, Free Co2, Turbidity. The result reveal that the range of variation in Different parameters was Temperature 28Oc to 30oc, PH 6.81 to7.08, conductivity 0.048 t0 0.067umhos/cm, BOD 1.16 to 1.89mg/L, Hardness 60.00 to 92.9 mg/L, Free Co2 1.11 to 4.03mg /L, Turbidity 0.002 to 0.009 mg/L. All the parameters are within the limit of range compared with WHO and ISI and the lake water is not polluted.